External Auditors' Perception of Cloud Computing Use in Indonesia : A Study of Non-Big Four CPA Firm in Bali - Bevi Libraeni; Mila Rosa Desmayani (PT. Altaf Publishing Corp, 2025)
This study explores how cloud computing services enhance audit performance from the perspective of external auditors, focusing on factors influencing adoption among non-Big Four public accounting firms (PAFs). Employing a qualitative approach with an interpretive paradigm, data were collected through in-depth interviews and document analysis. A total of eight external auditors from non-Big Four PAFs in Bali participated in the study. The findings reveal that auditors perceive cloud computing as beneficial due to its ease of access, system reliability, enhanced information sharing, and improved data security. One participant stated,